Evaluation of esophageal motility after endoscopic submucosal dissection for superficial esophageal cancer. Issue 10 (October 2015) - Takahashi, Kazuya; Takeuchi, Manabu; Sato, Yuichi; Sato, Hiroki; Mizuno, Kenichi; Hashimoto, Satoru; Kobayashi, Masaaki; Terai, Shuji
<x xml:space="preserve">Abstract</x> Introduction Endoscopic submucosal dissection (ESD) is a standard treatment for superficial esophageal cancer. Some patients complain of dysphagia after ESD even without any postoperative strictures. Although ineffective esophageal motility might be associated with dysphagia after ESD, its effect on esophageal motility after ESD remains unknown. Therefore, we aimed to elucidate esophageal motility after ESD and the cause of dysphagia using high-resolution manometry (HRM). Patients and methods Seventy-six patients (men/women, 64/12; mean age, 71.2 years) who had undergone ESD for superficial esophageal cancer were enrolled. The results of ESD were retrospectively investigated using endoscopic images from the ESD and patient questionnaire for dysphagia. Each patient underwent HRM, and the results were evaluated using metrics and contraction patterns, according to the Chicago classification. Results Data were obtained from 71 patients. The circumferential mucosal defect ratio (β=0.284, P=0.017), number of ESD (β=0.346, P=0.003), and number of endoscopic balloon dilatations (EBDs) (β=0.416, P<0.001) were correlated with the number of weak contraction with large breaks on HRM. The circumferential mucosal defect (odds ratio=1.074, P<0.001) and number of EBDs (odds ratio=1.200, P=0.035) were also significant predictors for dysphagia after ESD. Conclusion Circumferential mucosal defect ratio, EBD, and repeated ESD were predictors for impaired esophageal motility after ESD. Because circumferential mucosal defect ratios and EBD were also correlated with dysphagia after ESD, impaired esophageal motility could explain dysphagia after ESD.